Program report for 1997 - IRRI (IRRI, 1998)
The book presents the reports about irrigated rice ecosystem, rainfed lowland rice system, upland rice ecosystem, flood-prone rice ecosystem, cross-ecosystems research, germplasm conservation and dissemination, information and knowledge exchange, training, and strengthening international partnerships